2015
DOI: 10.1088/1752-7155/9/4/047110
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of sampling bags for the analysis of volatile organic compounds in breath

Abstract: Nalophan, Tedlar and Cali-5-Bond polymeric bags were compared to determine the most suitable type for breath sampling and storage when volatile organic compounds are to be determined. Analyses were performed by thermal desorption gas chromatography mass spectrometry. For each bag, the release of contaminants and the chemical stability of a gaseous standard mixture containing eighteen organic compounds, as well as the CO2 partial pressure were assessed. The selected compounds were representative of breath const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
71
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 34 publications
(54 reference statements)
5
71
0
Order By: Relevance
“…Hence, to determine the background contamination level on the m / z signals of interest, clean and flushed bags were filled with nitrogen and measured in scan mode by PTR‐MS after 0 and 72 h. On the first day, a few chemical compounds were detected in the blank bags at low concentration levels (<10 nL L −1 ), whereas for Tedlar, elevated levels of N,N‐dimethylacetamide (DMAC, m / z 88) and phenol ( m / z 95) were found. This corresponds well with the findings of previous studies (Pet'ka et al, 2000; Steeghs et al, 2007; Beauchamp et al, 2008; Ghimenti et al, 2015; Mochalski et al, 2013). During the 72‐h period, some m / z signals were found to increase, possibly due to off‐gassing from the polymer material or equilibration with room air due to diffusion.…”
Section: Methodssupporting
confidence: 93%
“…Hence, to determine the background contamination level on the m / z signals of interest, clean and flushed bags were filled with nitrogen and measured in scan mode by PTR‐MS after 0 and 72 h. On the first day, a few chemical compounds were detected in the blank bags at low concentration levels (<10 nL L −1 ), whereas for Tedlar, elevated levels of N,N‐dimethylacetamide (DMAC, m / z 88) and phenol ( m / z 95) were found. This corresponds well with the findings of previous studies (Pet'ka et al, 2000; Steeghs et al, 2007; Beauchamp et al, 2008; Ghimenti et al, 2015; Mochalski et al, 2013). During the 72‐h period, some m / z signals were found to increase, possibly due to off‐gassing from the polymer material or equilibration with room air due to diffusion.…”
Section: Methodssupporting
confidence: 93%
“…Analysis was performed within 20 minutes to avoid diffusive losses through the bag material, although previous studies have shown that such losses are not significant for wide-ranging compound types over a storage period of 24 hours. (see [16]). The room air was routinely analysed prior to coupling the sample bag to the SIFT-MS instrument.…”
Section: Breath Analysismentioning
confidence: 96%
“…Exhaled breath and breath condensate contain different volatile and nonvolatile fractions that provide complementary but different chemical information, and therefore each phase should be analyzed with specifically suitable methodology. In comparison to exhaled breath gas [30, 31], EBC contains more stable metabolomic content and allows easier sample manipulation, transfer, and storage [28]. …”
Section: Introductionmentioning
confidence: 99%